Importing High Food Prices by Exporting : Rice Prices in Lao PDR - Durevall, Dick; van der Weide, Roy (World Bank Group, Washington, DC, 2014)
This paper shows how a developing country, Lao PDR, imports high glutinous rice prices by exporting its staple food to neighboring countries, Vietnam and Thailand. Lao PDR has extensive export controls on rice, generating a sizable difference between domestic and international prices. Controls are relaxed after good harvests, leading to a surge in exports early in the season and rapidly rising prices later in the year. There is thus a strong case for removal of trade restrictions since they give rise to price spikes, keep the long-term price of glutinous rice low, and thereby hinder increases in income from agriculture. Although this is a case study of Lao PDR, the findings may equally apply to other developing countries that export their staple food.